2022
DOI: 10.3389/fmolb.2022.952626
|View full text |Cite
|
Sign up to set email alerts
|

Identification of COVID-19-Specific Immune Markers Using a Machine Learning Method

Abstract: Notably, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has a tight relationship with the immune system. Human resistance to COVID-19 infection comprises two stages. The first stage is immune defense, while the second stage is extensive inflammation. This process is further divided into innate and adaptive immunity during the immune defense phase. These two stages involve various immune cells, including CD4+ T cells, CD8+ T cells, monocytes, dendritic cells, B cells, and natural killer cells. Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 93 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…These algorithms included LASSO (Ranstam and Cook, 2018), LightGBM (Ke et al, 2017), MCFS (Dramiński and Koronacki, 2018), mRMR (Peng et al, 2005), and PFI (Fisher et al, 2019). These methods have been widely practiced in solving life science problems (Zhao et al, 2018;Li et al, 2022a;Li et al, 2022b;Li Z. et al, 2022;Lu et al, 2022;Huang et al, 2023a;Huang et al, 2023b).…”
Section: Feature Ranking Algorithmsmentioning
confidence: 99%
“…These algorithms included LASSO (Ranstam and Cook, 2018), LightGBM (Ke et al, 2017), MCFS (Dramiński and Koronacki, 2018), mRMR (Peng et al, 2005), and PFI (Fisher et al, 2019). These methods have been widely practiced in solving life science problems (Zhao et al, 2018;Li et al, 2022a;Li et al, 2022b;Li Z. et al, 2022;Lu et al, 2022;Huang et al, 2023a;Huang et al, 2023b).…”
Section: Feature Ranking Algorithmsmentioning
confidence: 99%
“…Thus, in this study, four feature-ranking algorithms, including last absolute shrinkage and selection operator (LASSO) [13], light gradient boosting machine (LightGBM) [14], Monte Carlo feature selection (MCFS) [15], and mRMR [16], were adopted to process the single-cell data on each cell type. These methods have been recognized in the life sciences [17][18][19][20][21][22][23][24]. As they are designed following different principles, the simultaneous use of them can provide more chances to extract essential gene features.…”
Section: Feature-ranking Algorithmsmentioning
confidence: 99%
“…In a clinical study in pregnant women, researchers found an increased proportion of CD8 + T cells and a high expression of MT2A in the cells of pregnant women positive for HBsAg and HBeAg [50]. With the use of a machine-learning-based approach to explore the characteristic immunomarkers of COVID-19, researchers found that CD8 + T cells in COVID-19 patients have specific MT2A up-regulation possibly by regulating intracellular metal homeostasis to influence the response of T cells to the SARS-CoV-2 infection [18].…”
Section: T-cell Features Associated With the Severity Of Covid-19mentioning
confidence: 99%
“…One of the most important aspects related to COVID-19 is the cytokine storm, during which various inflammatory cytokines are developed, and the consequent cytokine release syndrome (CRS), which represents an acute attack of excessive cytokines from the immune system triggered by inflammatory responses and the immunity ( 96 , 97 ). The CRS is characterized by high fever, erythema, edema, extreme fatigue, and nausea, which may also be associated with sepsis and multiple organ failure ( 98 ).…”
Section: Immunomodulation Of Covid-19 and Lung Cancermentioning
confidence: 99%